Die Bantu-Philosophie von Tempels aus afrikanischer Perspektive - Malibabo, Balimbanga (AAeO - Afrikanistik-Aegyptologie-Online, 2006)
The study presents Placide Temples’ way towards the “Philosophie bantoue” and the repercussion of the latter in the African discourse. Three decisive aspects are investigated: first the prehistory, i.e., the socio-political, scientific and religious contexts, which prepared him and put him in an estate to discover that Africans do have a Philosophy, second his purposefulness and his singularity, and finally the history of its reception and the reactions by the African scholars and sages.